A distinct octamer-binding protein present in malignant melanoma cells. - Cox, P; Temperley, S; Kumar, H; Goding, C (1988)
The octamer-binding proteins present in HeLa cells, B-cells and malignant melanoma cells were compared by a gel-electrophoresis DNA-binding assay. Using an extract from the malignant melanoma cells a complex was formed using a variety of octamer containing probes that was distinct from those found using either a HeLa or B-cell extract. DNAase 1 footprints and methylation interference patterns of the melanoma-specific octamer-binding protein were indistinguishable from those obtained with the HeLa factor NF-A1, except for preferential binding of the melanoma-specific factor to DNA methylated at two G residues 16 base-pairs 3' to the octamer motif. Competition analyses using a variety of wild-type and mutant probes showed that mutations affecting binding of NF-A1 similarly affected binding of the melanoma octamer-binding factor. These data also revealed the extreme flexibility of the octamer-binding site, with one probe sharing only 4 bases with the 8 base consensus sequence binding efficiently.